Vascular complications associated with intraaortic balloon pump supported percutaneous coronary intervention (PCI) and clinical outcomes from the British Cardiovascular Intervention Society National PCI Database. Issue 1 (8th February 2021) - Kinnaird, Tim; Anderson, Richard; Gallagher, Sean; Sharp, Andrew S. P.; Farooq, Vasim; Ludman, Peter; Copt, Samuel; Curzen, Nicholas; Sirker, Alex; Nolan, Jim; Mamas, Mamas
Abstract: Introduction: The impact of a vascular complication (VC) in the setting of intraaortic balloon pump (IABP) supported PCI on clinical outcomes is unclear. Methods: Using data from the BCIS National PCI Database, multivariate logistic regression was used to identify independent predictors of a VC. Propensity scoring was used to quantify the association between a VC and outcomes. Results: Between 2007 and 2014, 9, 970 PCIs in England and Wales were supported by IABP (1.6% of total PCI), with 224 femoral VCs (2.3%). Annualized rates of a VC reduced as the use of radial access for PCI increased. The independent predictors of a VC included a procedural complication (odds ratio [OR] 2.9, p < .001), female sex (OR 2.3, p < .001), PCI for stable angina (OR 3.47, p = .028), and use of a glycoprotein inhibitor (OR 1.46 [1.1:2.5], p = .04), with a lower likelihood of a VC when radial access was used for PCI (OR 0.48, p = .008). A VC was associated with a higher likelihood of transfusion (OR 5.7 [3.5:9.2], p < .0001), acute kidney injury (OR 2.6 [1.2:6.1], p = .027), and periprocedural MI (OR 3.2 [1.5:6.7], p = .002) but not with adjusted mortality at discharge (OR 1.2 [0.8:1.7], p = .394) or 12‐months (OR 1.1 [0.76:1.56], p = .639). In sensitivity analyses, there was a trend towards higher mortality in patients experiencing a VC who underwent PCI for stable angina (OR 4.1 [1.0:16.4], p value for interaction .069). Discussion and Conclusions Although in‐hospital morbidity was observed to be adversely affected by occurrence of a VC during IABP‐supported PCI, in‐hospital and 1‐year survival were similar between groups.